The Effect of The Internal Control System, Leadership Style, Organizational Culture, Organizational Commitment, and Good Government Governance on The Performance of The Local Government (Survey on All SKPD in Magelang Regency) - Jatmiko, Bambang; Gusmayanti, Deviana (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
This research aims to test and prove the effectiveness of the principle of the internal control system, leadership style, organizational culture, organizational commitment, and good government governance on the performance of the local government of Magelang Regency. As for the problem in this research, the work program in the regional work unit in Magelang Regency is very low and not efficient. This study used a survey to collect the data. The object of this research is the Regional Work Unit (SKPD) of Magelang Regency. The sample of this study is all SKPD in Magelang Regency, with a total of 20 SKPD. The analytical tool used in this research is regression analysis. This study found that the internal control system, leadership style, organizational culture, organizational commitment, and good government governance positively affect the performance of local governments.